An institutional explanation of the role of legislature accountability in local government budgetary decision-making / Mursal Salam … [et al.] - Salam, Mursal; Abd Rahman, Muhd Fauzi; Syed Yusuf, Sharifah Norzehan; Said, Jamaliah; Kirana Jaya, Wihana (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2022)
Legislature plays an important role to ensure accountability in the budgetary decision-making of the Indonesian local government. The legislature’s accountability role in budgetary decision-making concerns the Indonesian local government. Thus, this research investigated the legislature’s accountability role in the budgeting process and institution’s budgetary decision-making. It also examined the planning and budgeting documents in the budget policy-making by the legislature from the Institutional perspective. This research used a qualitative approach and selected three (3) local governments in Indonesia as case study sites. The three case study sites selected represented local governments with high, medium and low fiscal capacity. Data were collected using interviews with 19 budget actors from the three case study sites. The findings revealed institutional weaknesses in the form of norms and rules about legislature in their regional decisions. The regional decision-making and discussions or forums on budget spending and financing among the legislature were found to be politically driven and lacked focus on technical matters such as value for money. The findings of this research provide some basis for strengthening the regulation by central government authorities regarding the role of the legislature in decision- making based on the principles of transparency and accountability.